The Samoan Side: How Sia Figiel Debunks Orientalism In Where We Once Belonged - Abubakar, Sadiya (Penerbit Universiti Sains Malaysia (USM Press), 2018)
The result of the frst (and the subsequent) contact between the West and the East is an Oriental documentation, colonial establishment and notional subject-making of the East by the supposedly civilised and advanced West. Like all Orients, the Pacifc has been much represented and made subjects of theoretical discourses, characterised as bare-breasted and sexually available women, murderous and lecherous men, idly tropical islands inhabited by primitive people with little or no culture. Samoa has, specifcally, been a subject of anthropological discourse for many decades, following the Mead-Freeman controversy. Margaret Mead concludes that in Samoa, the transition from childhood, through adolescence, and into adulthood was one of relative ease and that sexuality is so free that women usually defer marriage to enjoy casual sex. Derek Freeman questions Mead’s fndings, gives contrary views and unifed the whole Samoan Islands as one and same. However, some Samoan (and non-Samoan) academics, writers and researchers debunk such Oriental representations. This paper analyses Sia Figiel’s explication of Samoa in Where We Once Belonged as a response to these Western anthropological studies and assertions on Samoan sexuality, coming-of-age, and the unifcation of Samoan Islands and overgeneralisations of Samoans’ dispositions. It argues that such claims are not so accurate but rather, made up of exaggerated instances and furnished imaginations for foregrounding Orientalism.